Frequency and Intensive Care Related Risk Factors of Pneumothorax in Ventilated Neonates. (27th April 2014) - Bhat Yellanthoor, Ramesh; Ramdas, Vidya
Abstract : Objectives . Relationships of mechanical ventilation to pneumothorax in neonates and care procedures in particular are rarely studied. We aimed to evaluate the relationship of selected ventilator variables and risk events to pneumothorax. Methods . Pneumothorax was defined as accumulation of air in pleural cavity as confirmed by chest radiograph. Relationship of ventilator mode, selected settings, and risk procedures prior to detection of pneumothorax was studied using matched controls. Results . Of 540 neonates receiving mechanical ventilation, 10 (1.85%) were found to have pneumothorax. Respiratory distress syndrome, meconium aspiration syndrome, and pneumonia were the underlying lung pathology. Pneumothorax mostly (80%) occurred within 48 hours of life. Among ventilated neonates, significantly higher percentage with pneumothorax received mandatory ventilation than controls (70% versus 20%;P < 0.01 ). Peak inspiratory pressure >20 cmH 2 O and overventilation were not significantly associated with pneumothorax. More cases than controls underwent care procedures in the preceding 3 hours of pneumothorax event. Mean airway pressure change (P = 0.052 ) and endotracheal suctioning (P = 0.05 ) were not significantly associated with pneumothorax. Reintubation (P = 0.003 ), and bagging (P = 0.015 ) were significantly associated with pneumothorax. Conclusion . Pneumothorax among ventilated neonates occurred at low frequency. Mandatory ventilation and selected care procedures in the preceding 3 hours had significant association.